Optimization variables in the polymetallic flotation using MINITAB-Hilarion Milpo Mining Project - Chia Aquije, Juan (2013)
Under the Convention Minera Milpo-San Marcos activities they were developed in order to motivate students of the race of Metallurgical Engineering and involve them in the testing mineralesy flotation treatment of the results using the statistical software MINTAB , with the materials from ore mining project Hilarion of Cia. de Minas Milpo. 22 addressed the factorial design aimed to optimize the recovery and concentrate grade rougher-scavenger Lead-zinc. The metallurgical performance was acceptable to the head reported law; however it became clear that optimizing the flotation conditions, you may get better results. The results give the MINITAB software, then run the factorial design 2 indicate that the equations governing the recovery of zinc are:Retrieve. Zn = 33.44 -1.66 [Z11] + 11.01 [CuSO4] + 4.08 [ZDegree of conc. Zn = 31442-1467 [Z1111] [CuSO] + 942 [CuSO4] + 1.053 [Z4] (1.0) 11] [CuSO4] (2.0) ^ 2According to surface charts provided by MINITAB, the point where better performance is achieved is to mayoresvalores xanthate and copper sulfate, taking better on the top right diseñofactorial Square. So we recommend further research to increase to higher values could be 11 a19 g / t Xanthate and 300 to 400 g / t of copper sulfate.